Cinema Entertainment : essays on audiences, films and film-makers - Lovell, Alan, 1935-; Sergi, Gianluca (Maidenhead, England ; New York : Open University Press, 2009)
Entertainment is a defining feature of contemporary culture, yet it is often accused of being superficial and even harmful. The authors challenge this negative view and argue for a reconsideration of the value of entertainment and the effect it has on the world in which we live.
What audiences go for : elite and mass taste -- Sensual pleasure, audiences, and The dark knight -- Alfred Hitchcock : the entertainer becomes an artist -- Stephen Spielberg, Indiana Jones, and the Holocaust -- The perspective of entertainers? Interviews with Randy Thom and Walter Murch -- The entertainment discourse.
Includes bibliographical references (p. [131]-133) and index.
Keywords: Motion pictures -- Social aspects; Motion pictures -- United States -- History